Analysis of the brain mural cell transcriptome - He, Liqun; Vanlandewijck, Michael; Raschperger, Elisabeth; Andaloussi Mäe, Maarja; Jung, Bongnam; Lebouvier, Thibaud; Ando, Koji; Hofmann, Jennifer; Keller, Annika; Betsholtz, Christer (Scientific reports, 2016)
Pericytes, the mural cells of blood microvessels, regulate microvascular development and function and have been implicated in many brain diseases. However, due to a paucity of defining markers, pericyte identification and functional characterization remain ambiguous and data interpretation problematic. In mice carrying two transgenic reporters, Pdgfrb-eGFP and NG2-DsRed, we found that double-positive cells were vascular mural cells, while the single reporters marked additional, but non-overlapping, neuroglial cells. Double-positive cells were isolated by fluorescence-activated cell sorting (FACS) and analyzed by RNA sequencing. To reveal defining patterns of mural cell transcripts, we compared the RNA sequencing data with data from four previously published studies. The meta-analysis provided a conservative catalogue of 260 brain mural cell-enriched gene transcripts. We validated pericyte-specific expression of two novel markers, vitronectin ( Vtn ) and interferon-induced transmembrane protein 1 ( Ifitm1 ), using fluorescent in situ hybridization and immunohistochemistry. We further analyzed signaling pathways and interaction networks of the pericyte-enriched genes in silico . This work provides novel insight into the molecular composition of brain mural cells. The reported gene catalogue facilitates identification of brain pericytes by providing numerous new candidate marker genes and is a rich source for new hypotheses for future studies of brain mural cell physiology and pathophysiology.